Učenje tujih jezikov z vidika staršev iz različnih slovenskih regij - Lešnik, Sabina; Ivanuš Grmek, Milena; Brumen, Mihaela (Revija za elementarno izobraževanje, 2013)
Views of Parents from Different Regions Across Slovenia on Learning Foreign Languages. This paper discusses the views of parents from four statistical regions of Slovenia (Mura, Drava, Central Slovenia, and Gorizia) on foreign language learning. First, we introduce some theories on learning and teaching foreign languages at the primary level and define the role of parents in foreign language education. Further on, we provide the results of an empirical research study which took place in 2012 and the goal of which was to examine what parents of students in the ninth grade of Slovenian primary schools thought about language learning. Based on the survey results, we found that the majority of parents had a positive attitude toward foreign language learning. Furthermore, there was a statistically significant difference among parents coming from different Slovenian regions with regard to foreign language learning.
Keywords: foreign languages; parents’ attitudes; primary school; statistical regions of Slovenia